PENGARUH SISA ANGGARAN, PENDAPATAN ASLI DAERAH, DANA BAGI HASIL, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL FUNGSI PENDIDIKAN (STUDI PADA PEMERINTAH DAERAH KABUPATEN/KOTA DI ACEH) - Febriani, Diah; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The Purpose of this research is to determine whether there is influence financing surplus, own revenue, Profit Sharing Fund, General Allocation Fund, and Special Allocation Fund to the Capital Expenditure of education function. The data is the secondary data which has been obtained from the Realization of Local Goverment Budged report of 23 districts/cities in Aceh Province and the observation is in 2013-2015 periods in order to obtain 69 units. The model analysis instrument thet has been employed in this research is Multiple Linear Regressions Analysis. The results showed that Financing Surplus has influence to the Capital Expenditure of Education, Own Revenue has influence to the Capital Expenditure of Education, Profit Sharing Fund has influence to the Capital Expenditure of Education, General Allocation Fund has influence to the Capital Expenditure of Education, and Special Allocation Fund has influence to the Capital Expenditure of Education.